Organic silicon-fluorine polymer / nano inorganic particle composite coating and preparation method thereof
The surface of nano-inorganic particles is modified through reversible addition-fragmentation chain transfer (RAFT) interfacial polymerization technology to construct a composite coating of organosilicon fluoropolymer/nano-inorganic particles. This solves the problem of difficult uniform dispersion of inorganic particles in organic components, achieves excellent adhesion and corrosion resistance of the coating, and is suitable for surface protection of precision metal accessories.
Patent Information
- Application Number
- CN202510773614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-09-12
AI Technical Summary
Existing technologies make it difficult to construct a uniform organic/inorganic composite cross-linked network structure, which makes it difficult to evenly disperse inorganic particles in the organic components, affecting the adhesion, mechanical properties and corrosion resistance of the coating.
The reversible addition fragmentation chain transfer (RAFT) interfacial polymerization technology is used to modify the surface of the nano-inorganic particles, graft the R group of thiocarbonate, and copolymerize with the organic silicon fluoropolymer to form a composite coating with a regular core-shell structure, and a uniform chemical cross-linking network is formed through thermal cross-linking.
The excellent adhesion, mechanical properties and corrosion resistance of the organosilicon fluoropolymer/nano-inorganic particle composite coating are achieved, and it is suitable for the surface protection of precision metal accessories.
Smart Images

Figure BDA0005443658530000031 
Figure BDA0005443658530000032 
Figure BDA0005443658530000033
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, in particular to an organic silicon fluoropolymer / nano-inorganic particle composite coating and a preparation method thereof. Background Art
[0002] With the rapid development of industrial technology, precision metal accessories are widely used in aerospace, automobile manufacturing, electronic information and other fields, and the requirements for their surface protection are becoming increasingly higher. Corrosion resistance is a major problem commonly encountered in the application of metal materials. Precision metal accessories such as copper and aluminum are easily exposed to the air environment for a long time and easily react with oxygen and moisture in the air to cause corrosion, discoloration and other problems, affecting their appearance and performance. At the same time, in some industrial environments, precision metal accessories will come into contact with chemicals such as acids, alkalis, and salts, and are also easily corroded by them, causing performance damage. In addition, precision metal accessories are also prone to surface wear due to friction and collision during use, transportation, and assembly, reducing their service life.
[0003] Organic silicon fluoropolymer coatings have excellent corrosion resistance and stain resistance and are widely used in various corrosion protection fields. Inorganic coatings have the advantages of high surface hardness and good wear resistance. The organic / inorganic composite cross-linked coating obtained by combining the two can have the above advantages. Applying it to the surface of precision metal accessories can effectively solve the above problems. However, due to the poor compatibility and weak interaction between inorganic and organic components, it is difficult for inorganic particles to be evenly dispersed in the organic component. Existing methods mostly modify the surface of inorganic particles to introduce olefinic double bonds, and participate in copolymerization reactions to achieve covalent connection between inorganic particles and organic components. However, due to the kinetic mechanism of traditional free radical polymerization, it is difficult to construct a uniform organic / inorganic composite cross-linked network structure, which affects the performance of the coating. Therefore, how to construct an organic / inorganic composite cross-linked coating with good adhesion, mechanical properties, corrosion resistance, stain resistance and other advantages through component selection and structural design is an important challenge facing the surface protection of precision metal accessories. Summary of the Invention
[0004] (1) Technical problems solved
[0005] In view of the deficiencies in the prior art, the present invention provides an organosilicon fluoropolymer / nano-inorganic particle composite coating and a preparation method thereof.
[0006] (2) Technical solution
[0007] To achieve the purpose of the present invention, the following technical solutions are adopted:
[0008] A composite coating of organosilicon fluoropolymer / nano-inorganic particles is characterized in that it is prepared by reversible addition fragmentation chain transfer (RAFT) interfacial polymerization, and the preparation method is as follows:
[0009] Dissolve 0.1-0.5 parts by weight of an initiator in 20-60 parts by weight of an organic solvent, then add 5-30 parts by weight of surface-modified nano-inorganic particles, 10-30 parts by weight of a trimethoxysilyl acrylate monomer, and 10-30 parts by weight of a fluorinated acrylate monomer, stirring and dispersing the mixture evenly. Heat to 50-80°C under nitrogen, polymerize for 3-6 hours, and terminate the reaction to obtain a composite coating of organosilicon-fluoropolymer / nano-inorganic particles.
[0010] The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.
[0011] The organic solvent is one or more of ethanol, acetone and acetonitrile.
[0012] The preparation method of the surface-modified nano-inorganic particles is as follows: 0.5-2 parts by weight of the nano-inorganic particles are added to 50-200 parts by weight of a 50wt% ethanol aqueous solution, and after ultrasonic dispersion, the pH value of the dispersion is adjusted to 4-6 with acetic acid, and then 0.05-0.4 parts by weight of thiocarbonate is added. The mixture is continuously stirred and reacted at 80°C for 5-8 hours. The product is centrifuged, and the supernatant is dried to obtain the surface-modified nano-inorganic particles.
[0013] The nano-inorganic particles used in the surface-modified nano-inorganic particle preparation method are one or both of nano-SiO2 and nano-TiO2.
[0014] The structural formula of the thiocarbonate compound used in the preparation method of the surface-modified nano-inorganic particles is shown in formula (I):
[0015]
[0016] The structures of the Z group are shown in formulas (II), (III), and (IV):
[0017]
[0018] The structure of the R group is shown in formula (V):
[0019]
[0020] The trimethoxysilyl acrylate monomer is one or both of 3-(trimethoxysilyl)propyl acrylate and 3-(trimethoxysilyl)propyl methacrylate.
[0021] The fluorine-containing acrylic ester monomer is one or more of octafluoropentyl acrylate, octafluoropentyl methacrylate, and dodecafluoroheptyl methacrylate.
[0022] (3) Beneficial effects
[0023] Compared with the prior art, the present invention provides a composite coating of organosilicon fluoropolymer / nanoinorganic particles, which has the following beneficial effects: the present invention performs surface modification on the nanoinorganic particles, grafts the R group on the thiocarbonate to the surface of the nanoinorganic particles, and on this basis adopts the reversible addition-fragmentation chain transfer interfacial polymerization technology to construct a composite coating with a regular core-shell structure of organosilicon fluoropolymer-coated nanoinorganic particles. After coating, a subsequent thermal cross-linking reaction is performed to form an organosilicon fluoropolymer / nanoinorganic particle composite coating with a uniform chemically cross-linked network structure. The coating can be widely used in the surface protection of precision metal accessories materials, exhibits excellent adhesion, mechanical properties, stain resistance, corrosion resistance, etc., and has broad application prospects. DETAILED DESCRIPTION
[0024] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention are further described in detail below.
[0025] The composite coating of organosilicon fluoropolymer / nano-inorganic particles is applied to tinplate sheets, first placed in air at 60°C to allow the methoxysilyl groups to be fully hydrolyzed and converted into silanol groups, while most of the solvent is removed, and then vacuum-dried at 60°C to obtain a cross-linked and cured organosilicon fluoropolymer / nano-inorganic particle composite coating.
[0026] The adhesion of organosilicon fluoropolymer / nano-inorganic particle composite coatings was determined using a QFH cross-hatch tester according to GB / T 9286-1998.
[0027] The surface hardness of the organosilicon fluoropolymer / nano-inorganic particle composite coating was measured using a QHQ-A portable pencil scratch tester according to GB / T 6739-2006.
[0028] The flexibility of organosilicon fluoropolymer / nano-inorganic particle composite coatings was determined using a QTX paint film elasticity tester according to GB / T1731-93.
[0029] The impact resistance of organosilicon fluoropolymer / nano-inorganic particle composite coatings was determined using a QCJ120A paint film impactor according to GB / T 1732-93.
[0030] The water contact angle of the organosilicon fluoropolymer / nano-inorganic particle composite coating was measured using a GYJJ-12 contact angle meter.
[0031] The salt spray resistance of organosilicon fluoropolymer / nanoinorganic particle composite coating was determined using a Q-FOG SSP-600 cyclic corrosion salt spray chamber according to GB / T1771-2007.
[0032] Example 1:
[0033] A composite coating of organosilicon fluoropolymer / nano-inorganic particles is prepared by reversible addition fragmentation chain transfer (RAFT) interfacial polymerization. The preparation method of the composite coating is as follows:
[0034] Dissolve 0.3 parts by weight of initiator in 20 parts by weight of organic solvent, then add 15 parts by weight of surface-modified nano-inorganic particles, 10 parts by weight of trimethoxysilyl acrylate monomer, and 20 parts by weight of fluorinated acrylate monomer, stirring and dispersing them uniformly. Heat to 50°C under nitrogen, polymerize for 6 hours, and terminate the reaction to obtain an organosilicon-fluoropolymer / nano-inorganic particle composite coating.
[0035] The initiator is azobisisoheptanonitrile.
[0036] The organic solvent is ethanol.
[0037] The preparation method of the surface-modified nano-inorganic particles is as follows: 0.5 parts by weight of the nano-inorganic particles are added to 50 parts by weight of a 50wt% ethanol aqueous solution, and after ultrasonic dispersion, the pH value of the dispersion is adjusted to 4 with acetic acid, and then 0.2 parts by weight of thiocarbonate is added. The mixture is continuously stirred and reacted at 80°C for 5 hours. The product is centrifuged, and the supernatant is dried to obtain the surface-modified nano-inorganic particles.
[0038] The nano-inorganic particles used in the surface-modified nano-inorganic particle preparation method are nano-TiO2.
[0039] The structural formula of the thiocarbonate compound used in the method for preparing the surface-modified nano inorganic particles is shown in formula (I).
[0040] The structure of the Z group is shown in formula (II).
[0041] The structure of the R group is shown in formula (V).
[0042] The trimethoxysilyl acrylate monomer is 3-(trimethoxysilyl)propyl acrylate.
[0043] The fluorine-containing acrylic ester monomer is octafluoropentyl acrylate.
[0044] Example 2:
[0045] A composite coating of organosilicon fluoropolymer / nano-inorganic particles is characterized in that it is prepared by reversible addition fragmentation chain transfer (RAFT) interfacial polymerization, and the preparation method is as follows:
[0046] Dissolve 0.1 parts by weight of initiator in 20 parts by weight of organic solvent, then add 5 parts by weight of surface-modified nano-inorganic particles, 10 parts by weight of trimethoxysilyl acrylate monomer, and 10 parts by weight of fluorinated acrylate monomer, stirring and dispersing them uniformly. Heat to 80°C under nitrogen, polymerize for 3 hours, and terminate the reaction to obtain an organosilicon-fluoropolymer / nano-inorganic particle composite coating.
[0047] The initiator is azobisisobutyronitrile.
[0048] The organic solvent is acetone.
[0049] The preparation method of the surface-modified nano-inorganic particles is as follows: 2 parts by weight of the nano-inorganic particles are added to 200 parts by weight of a 50wt% ethanol aqueous solution, and after ultrasonic dispersion, the pH value of the dispersion is adjusted to 6 with acetic acid, and then 0.4 parts by weight of thiocarbonate is added. The mixture is continuously stirred and reacted at 80°C for 8 hours. The product is centrifuged, and the supernatant is dried to obtain the surface-modified nano-inorganic particles.
[0050] The nano-inorganic particles used in the surface-modified nano-inorganic particle preparation method are nano-SiO2.
[0051] The structural formula of the thiocarbonate compound used in the method for preparing the surface-modified nano inorganic particles is shown in formula (I).
[0052] The structure of the Z group is shown in formula (III).
[0053] The structure of the R group is shown in formula (V).
[0054] The trimethoxysilyl acrylate monomer is 3-(trimethoxysilyl)propyl methacrylate.
[0055] The fluorine-containing acrylic ester monomer is octafluoropentyl methacrylate.
[0056] Example 3:
[0057] A composite coating of organosilicon fluoropolymer / nano-inorganic particles is characterized in that it is prepared by reversible addition fragmentation chain transfer (RAFT) interfacial polymerization, and the preparation method is as follows:
[0058] Dissolve 0.5 parts by weight of initiator in 60 parts by weight of organic solvent, then add 30 parts by weight of surface-modified nano-inorganic particles, 30 parts by weight of trimethoxysilyl acrylate monomer, and 30 parts by weight of fluorinated acrylate monomer, stirring and dispersing them uniformly. Heat to 80°C under nitrogen, polymerize for 6 hours, and terminate the reaction to obtain an organosilicon-fluoropolymer / nano-inorganic particle composite coating.
[0059] The initiator is dibenzoyl peroxide.
[0060] The organic solvent is acetonitrile.
[0061] The preparation method of the surface-modified nano-inorganic particles is as follows: 2 parts by weight of the nano-inorganic particles are added to 200 parts by weight of a 50wt% ethanol aqueous solution, and after ultrasonic dispersion, the pH value of the dispersion is adjusted to 4 with acetic acid, and then 0.05 parts by weight of thiocarbonate is added. The mixture is continuously stirred and reacted at 80°C for 5 hours. The product is centrifuged, and the supernatant is dried to obtain the surface-modified nano-inorganic particles.
[0062] The nano-inorganic particles used in the surface-modified nano-inorganic particle preparation method are nano-SiO2.
[0063] The structural formula of the thiocarbonate compound used in the method for preparing the surface-modified nano inorganic particles is shown in formula (I).
[0064] The structure of the Z group is shown in formula (IV).
[0065] The structure of the R group is shown in formula (V).
[0066] The trimethoxysilyl acrylate monomer is 3-(trimethoxysilyl)propyl acrylate.
[0067] The fluorine-containing acrylic ester monomer is dodecafluoroheptyl methacrylate.
[0068] Comparative Example 1
[0069] A composite coating of organosilicon fluoropolymer / nano-inorganic particles is prepared by conventional free radical polymerization. The preparation method is as follows:
[0070] Dissolve 0.3 parts by weight of initiator in 20 parts by weight of organic solvent, then add 15 parts by weight of surface-modified nano-inorganic particles, 10 parts by weight of trimethoxysilyl acrylate monomer, and 20 parts by weight of fluorinated acrylate monomer, stirring and dispersing them uniformly. Heat to 50°C under nitrogen, polymerize for 6 hours, and terminate the reaction to obtain an organosilicon-fluoropolymer / nano-inorganic particle composite coating.
[0071] The initiator is azobisisoheptanonitrile.
[0072] The organic solvent is ethanol.
[0073] The preparation method of the surface-modified nano-inorganic particles is as follows: 0.5 parts by weight of the nano-inorganic particles are added to 50 parts by weight of a 50wt% ethanol aqueous solution, and after ultrasonic dispersion, the pH value of the dispersion is adjusted to 4 with acetic acid, and then 0.2 parts by weight of 3-(trimethoxysilyl)propyl acrylate is added. The mixture is stirred continuously and reacted at 80°C for 5 hours. The product is centrifuged, and the supernatant is dried to obtain the surface-modified nano-inorganic particles.
[0074] The nano-inorganic particles used in the surface-modified nano-inorganic particle preparation method are nano-TiO2.
[0075] The trimethoxysilyl acrylate monomer is 3-(trimethoxysilyl)propyl acrylate.
[0076] The fluorine-containing acrylic ester monomer is octafluoropentyl acrylate.
[0077] The performance test results of the organosilicon fluoropolymer / nano-inorganic particle composite coatings described in Examples 1-3 and Comparative Example 1 are shown in Table 1.
[0078] Table 1
[0079]
[0080] As can be seen from Table 1, the organosilicone fluoropolymer / nanoinorganic particle composite coatings prepared by reversible addition-fragmentation chain transfer polymerization and traditional free radical polymerization are basically the same in flexibility and water contact angle, but the former has better adhesion, higher pencil hardness and impact resistance, and better salt spray resistance. This shows that the use of reversible addition-fragmentation chain transfer polymerization interface technology can regulate the microstructure of the composite coating, thereby obtaining more excellent performance. Therefore, the organosilicone fluoropolymer / nanoinorganic particle composite coating prepared by the present invention has broad application prospects.
[0081] The above embodiments are merely examples for the purpose of clearly illustrating the present invention and are not intended to limit the embodiments of the present invention. Those skilled in the art will appreciate that other variations or modifications may be made based on the above description. It is not necessary and impossible to enumerate all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention are intended to be included within the scope of protection of the claims of the present invention.
Claims
1. A composite coating of organosilicon fluoropolymer / nano-inorganic particles, characterized in that: The preparation is carried out by reversible addition fragmentation chain transfer (RAFT) interfacial polymerization, and the preparation method is as follows: Dissolve 0.1-0.5 parts by weight of an initiator in 20-60 parts by weight of an organic solvent, then add 5-30 parts by weight of surface-modified nano-inorganic particles, 10-30 parts by weight of a trimethoxysilyl acrylate monomer, and 10-30 parts by weight of a fluorinated acrylate monomer, stirring and dispersing the mixture evenly. Heat to 50-80°C under nitrogen, polymerize for 3-6 hours, and terminate the reaction to obtain a composite coating of organosilicon-fluoropolymer / nano-inorganic particles.
2. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.
3. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The organic solvent is one or more of ethanol, acetone and acetonitrile.
4. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The preparation method of the surface-modified nano-inorganic particles is as follows: 0.5-2 parts by weight of the nano-inorganic particles are added to 50-200 parts by weight of a 50wt% ethanol aqueous solution, and after ultrasonic dispersion, the pH value of the dispersion is adjusted to 4-6 with acetic acid, and then 0.05-0.4 parts by weight of thiocarbonate is added. The mixture is continuously stirred and reacted at 80°C for 5-8 hours. The product is centrifuged, and the supernatant is dried to obtain the surface-modified nano-inorganic particles.
5. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The nano-inorganic particles used in the surface-modified nano-inorganic particle preparation method are one or both of nano-SiO2 and nano-TiO2.
6. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The structural formula of the thiocarbonate compound used in the preparation method of the surface-modified nano-inorganic particles is shown in formula (I): The structures of the Z group are shown in formulas (II), (III), and (IV): C 12 H 25 S-(III)C4H9S-(IV) The structure of the R group is shown in formula (V):
7. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The trimethoxysilyl acrylate monomer is one or both of 3-(trimethoxysilyl)propyl acrylate and 3-(trimethoxysilyl)propyl methacrylate.
8. The organic silicon fluoropolymer / nano-inorganic particle composite coating according to claim 1, characterized in that: The fluorine-containing acrylic ester monomer is one or more of octafluoropentyl acrylate, octafluoropentyl methacrylate, and dodecafluoroheptyl methacrylate.